(untitled) (The International Journal for Scientific Research, 2026)
This study addresses the topic of "The Impact of Real Estate Registration on the Protection of Real Rights in the Saudi System: An Analytical Study in Light of the Saudi Civil Transactions Law and Modern Judicial Applications," considering it one of the most significant legislative transformations witnessed by real estate regulation in the Kingdom of Saudi Arabia. The study’s importance stems from the role of real estate registration in enhancing the stability of real estate ownership, protecting real rights, and achieving legal certainty in real estate transactions, aligning with the objectives of Saudi Vision 2030, which aims to develop and improve the efficiency of the real estate sector. The study aimed to clarify the legal nature of real estate registration, analyze its regulatory basis in the Kingdom of Saudi Arabia, and demonstrate its contribution to protecting real rights and stabilizing real estate ownership. It also examined the legal validity of registration in the real estate registry and its legal implications for third parties, and analyzed the trends in Saudi jurisprudence regarding real estate disputes related to real estate registration. Furthermore, the study sought to identify the most prominent practical problems that may arise from discrepancies between the data recorded in the real estate registry and the actual state of ownership. The study adopted a descriptive-analytical approach, supported by inductive and comparative methods as required by the nature of the research. This was achieved through an analysis of relevant legal texts pertaining to the Real Estate Registration System and the Saudi Civil Transactions Law, and by examining recent judicial applications related to the legal validity of the real estate register and the protection of real property rights. The study concluded that the Real Estate Registration System is an effective legal tool for enhancing the protection of real property rights and ensuring the stability of real estate transactions. This is accomplished by granting real estate registration strong evidentiary weight in proving and asserting ownership against third parties, and by reducing disputes related to ownership. The study also demonstrated that the Saudi judiciary is moving towards strengthening confidence in the real estate register while safeguarding rights acquired prior to registration. The study recommended developing the legislative and procedural framework for real estate registration, enhancing its integration with the Civil Transactions Law, and unifying relevant judicial principles. This would contribute to raising the level of real estate security, supporting investment, and achieving sustainable development.